Financial And Economic Outlook for The Russia-India-China Triple Alliance - Valery V. SMIRNOV; Vladislav L. SEMENOV; Tamara V. TALANOVA; Anna N. ZAKHAROVA; Lyubov P. ROMANOVA (Communications of International Proceedings, 2023)
The study is based on a systematic approach using the method of statistical, neural network and cluster analysis. The paper hypothesizes the existence of a certain financial and economic perspective of the triple alliance of Russia-India-China, which allows us to assess the possibilities of the transition of the Russian economy from a catching-up model of development to a leading one. The paper establishes the high importance of the dynamics of the growth rates of indicators: Russia ‒ GDP based on the share of purchasing power parity in global volume and at current prices; for India ‒ primary net lending/borrowing of the public administration sector and GDP at current prices; China ‒ the volume of imports of goods, consumer inflation and total government revenues. The study reveals the possibilities of GDP growth of the Russia-India-China triple alliance by regulating the growth rate of total government revenues and the unemployment rate in the context of a significant difference in population growth rates. The article shows that the financial and economic perspective of the Russia-India-China triple alliance can be seen in the cumulative dynamics of GDP growth rates based on the share of purchasing power parity in the global volume and total government revenues.
Keywords: dynamics of indicators; development model; triple alliance; financial and economic perspective.